Bed Bunk Accommodation; Convergence of Online Promotion Media with Balinese Traditional Houses in Canggu Village, Bali - Ni Putu Suda Nurjani; Syamsul Alam Paturusi; Ngakan Ketut Acwin Dwijendra; I Dewa Gede Agung Diasana Putra (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2019)
Bali is one of the most popular tourism destinations in the world with various forms of accommodation. Start from five star hotels until small lodgings built in each community residential unit. The strong custom and restrictions on tall buildings in Bali, making people look for various new alternatives to develop accommodation. The existence of local regulations that require the use of traditional Balinese ornamentation, requires accommodation owners to find adaptive accommodation development methods. However, with the development of the digital industry 4.0 specifically in contact with online advertising, there are no official rules in Bali that regulate it. This condition makes the demand for cheap accommodation in Bali seem unlimited. The promotion system no longer requires government legality. This phenomenon makes accommodations in remote places even can be accessed easily by all people in the world. The community then competes with each other to build cheap accommodations in their traditional homes. The government also cannot touch the spatial development caused by online media demand, due to the absence of regulations that limit it. This research tries to identify the bed bunk phenomenon that is built and operationalized through online promotion media, and has no legality. Data collection was carried out by direct observation of the object of study in Canggu village, district of North Kuta, Badung Regency, Bali Province. The findings of this study indicate that, bed bunk was born in Bali due to the high demand for backpacker tourists which is sufficient with wifi, table and bed facilities. The high cost of land in Bali encourages local people to build accommodations in their residential units. The maximum utilization of the interior (construction of 6-8 beds in one room) is the most preferred choice. This condition is due to vertical building restrictions that cannot exceed 15m and economic factors (get maximum income on narrow land). This finding is expected to be used as an evaluation material for spatial improvement in Bali which has an impact on congestion throughout the tourist area due to uncontrolled accommodation development.